Test of Inhibitory Power of Virgin Coconut Oil and Olive Oil From Various Brands Against Staphylococcus aureus Bacteria, and The Review According to Islamic Prespective - fanni tasya rahma; Pratami Adityaningsari; Firman Arifandi (Junior Medical Journal, 2022)
Infectious disease is a major public health problem in developed and developing countries. One of the bacteria that can cause infection is Staphylococcus aureus. Along with an increase in bacterial resistance, one of which is caused by the inappropriate use of antibiotics, it reduces the effectiveness and performance of treatment methods. Alternative medicine can use pure coconut oil (virgin coconut oil) which contains lauric acid as an antibacterial and olive oil which contains oleuropein as an antibacterial. Experimental research using the Kirby Bauer diffusion disc method by measuring the diameter of the inhibition zone of Staphylococcus aureus bacteria. The materials tested were various types of pure coconut oil and olive oil on the market with 50%, 75% and 100% inhibition zones. In the inhibition test of virgin coconut oil and olive oil, the bacterial inhibition zone was only found at a concentration of 100%, while at a concentration of 50% and 75% there was no bacterial inhibition of the two tested materials. The conclusion is that there is an effect of virgin coconut oil and olive oil on the inhibition of Staphylococcus aureus bacteria at a concentration of 100%.